Effect of a weight loss intervention on iron parameters in overweight and obese Turkish women - Kaner, Gülşah; Pekcan, Ayla Gülden; Şarer Yürekli, Banu Pınar (Progress in Nutrition, 2019)
Background/aims: To examine changes in body weight and iron parameters of overweight and obese premenopausal women who participated in a weight loss intervention. Methods: A total of 147 overweight or obese women, aged 20-49 years, were included in this study. Subjects were divided into two groups at the baseline of study. All women underwent a 3 month intervention, a nutritional weight loss program. The first group included women with low hemoglobin levels, as the second group consisted of women with normal hemoglobin levels. Biochemical, and anthropometric parameters were measured, and dietary intake was recorded at the baseline and end of the study. Results: After the intervention, first group had 10.1% weight loss, whereas the second group had 10.7%. A statistically significant relationship between body weight loss and C-reactive protein (CRP) levels was determined. Significant decrease was observed on the anthropometric variables, dietary energy, total fat, saturated fatty acids, and carbohydrate intake. Dietary intakes of vitamin C, fiber, iron, and calcium levels increased. Conclusion: Weight loss improved the blood iron parameters and anthropometric measurements possibly due to its possitive effect on inflammation.